Modulation of established murine collagen-induced arthritis by a single inoculation of short-term lipopolysaccharide-stimulated dendritic cells. Issue 9 (4th December 2007) - Salazar, L; Aravena, O; Abello, P; Escobar, A; Contreras-Levicoy, J; Rojas-Colonelli, N; Catalán, D; Aguirre, A; Zúñiga, R; Pesce, B; González, C; Cepeda, R; et al.
Abstract : Background: The use of regulatory or immature dendritic cells (DCs) as tools for modulating experimental rheumatoid arthritis is very recent. Tumour necrosis factor (TNF)-stimulated DCs have been shown to restore tolerance in experimental autoimmune encephalomyelitis and collagen-induced arthritis (CIA). Objective: We investigated the capacity of short-term lipopolysaccharide (LPS)-stimulated DCs pulsed with type II collagen (CII) to induce tolerance against established CIA. Methods: Bone marrow-derived DCs were generated in the presence of granulocyte monocyte colony-stimulating factor (GM-CSF). After CIA induction, mice were injected at day 35 with a single dose of 4- or 24-h LPS-stimulated DCs that had been loaded with CII (4hLPS/CII/DCs or 24hLPS/CII/DCs). Arthritis progression was monitored by clinical and histological evaluations. Results: Flow cytometry of 4hLPS/CII/DCs showed intermediate CD40 and CD86 expression, lower than that of 24hLPS/CII/DCs (fully mature) and higher than that of CII/DCs (immature). A functional assay showed that 4hLPS/CII/DCs display increased endocytosis ability with respect to 24hLPS/CII/DCs, indicating a semimature state. The single inoculation of 4hLPS/CII/DCs in mice with established CIA reduced disease severity significantly over time. Histological evaluation of mice treated with 4hLPS/CII/DCs revealed diminished inflammatory synovitis, cartilage damage and fibrosis. Co-cultures of DCs with splenocytes from CIA mice showed that collagen-specific interferon (IFN)γ production was dramatically inhibited by 4hLPS/CII/DCs. 4hLPS/CII/DCs were high IL10 producers, which could explain the inhibition of arthritis progression in mice receiving this treatment because neither antibodies nor regulatory CD4+CD25+Foxp3+ T lymphocytes were demonstrated to be involved. Conclusion: Short-term LPS-modulated DCs inoculation interferes with CIA progression when loaded with CII.